Analysis and study of ZVI on the physical properties and microstructure of solidified oil sludge residue - Wang Shixin; Wu Yankai; Yan Fengmei; Wang Jianxin; Liu Zequn; Li Hongjie (Results in Engineering)
Oil sludge residue, a solid waste from thermal decomposition of oily sludge in petroleum production, lacks properties suitable for engineering use. This study solidified it using cement (OC), cement with steel slag powder (OC-SSP), and cement with fly ash (OC-F). Through unconfined compressive strength (UCS) and pH testing, optimal mix proportions meeting engineering requirements were identified. Subsequently, nano zero-valent iron (nZVI) loaded biochar (BC) was added in varying amounts for comparative tests. The effects of mix proportions and curing age on solidification were evaluated using UCS, pH, and toxicity tests. Scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) examined microstructural changes and solidification feasibility. Results showed that higher steel slag powder and fly ash proportions significantly increased sample strength. The pH rose with increased cement and steel slag powder but decreased with more fly ash. Adding nZVI-BC improved early-stage strength and reduced pH, though it had minimal impact on later-stage strength. Post-treatment, the solidified residue met toxicity management standards. Microstructural analysis revealed that solidifying agents promoted the formation of reticular hydrated gel products, enhancing microstructural compactness. This provides a scientific foundation and practical reference for optimizing oil sludge residue solidification. The study demonstrates that combining cement with steel slag powder, fly ash, and nZVI-BC can effectively improve the engineering viability of residual while addressing environmental concerns, offering a sustainable approach to managing this petroleum industry byproducts.